2013
DOI: 10.4028/www.scientific.net/amr.739.537
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dimethyl Ether in Air by Cataluminescence-Based Gas Sensor

Abstract: A rapid and sensitive cataluminescence-based gas sensor utilizing nanosized Y2MnO5as the sensing materials for determining dimethyl ether in air was proposed. The luminescence characteristics and the optimal conditions were investigated in detail. The gas sensor showed high selectivity for dimethyl ether at 620 nm and satisfying activity at 210°C under the optimized conditions. The linear range of cataluminescence intensity versus concentration of dimethyl ether was 5~120 mg/m3, and the detection limit (3σ) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The peony‐like Na 2 Mg(CO 3 ) 2 was prepared by the hydrothermal method [16]. MgSO 4 ·7H 2 O and Na 2 CO 3 were dissolved in a beaker containing 100 ml of Mili‐Q water at a molar ratio of 1:5 and stirred vigorously for 30 min with a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peony‐like Na 2 Mg(CO 3 ) 2 was prepared by the hydrothermal method [16]. MgSO 4 ·7H 2 O and Na 2 CO 3 were dissolved in a beaker containing 100 ml of Mili‐Q water at a molar ratio of 1:5 and stirred vigorously for 30 min with a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…The metallic elements of sodium and magnesium, abundant in nature, are cheap and easily available, and many studies have shown that MgO has good CTL properties and can be used for the detection of volatile organic compounds [16]. Based on this, peony‐like Na 2 Mg(CO 3 ) 2 was prepared by hydrothermal method for the detection of alcohols.…”
Section: Introductionmentioning
confidence: 99%